Miscibility of Poly(vinylidene fluoride) and Cellulose Acetate Blends in Dimethyl Formamide - Selva Kumar, M.; Krishna Bhat, D. (Asian Journal of Chemistry, 2010)
The miscibility of poly(vinylidene fluoride) (PVDF) and cellulose acetate blends in dimethyl formamide has been investigated by viscosity, density, refractive index and ultrasonic velocity studies. The polymer-solvent and blend-solvent interaction parameters and heat of mixing have been calculated using the viscosity, density and ultrasonic velocity data. The results indicated the existence of positive interactions in the blend polymer solutions and that they are miscible in dimethyl formamide in the entire composition range between 303-323 K. The study also revealed that the variation in the temperature does not affect the miscibility of poly(vinylidene fluoride) and cellulose acetate blends in DMF significantly. The presence of hydrogen bonding in the blends in the solid state has also been indicated by FTIR studies. SEM images also supported the miscibility of blends.